Varying orientations to sharing life stories: A diachronic study of Japanese women's discourse. (September 2022) - Nakane, Ikuko; Okano, Kaori; Maree, Claire; Takagi, Chie; Tanaka, Lidia; Iwasaki, Shimako
Abstract: Language change across the lifespan is relatively underexplored in sociolinguistics. While studies of individuals' language across life stages are often considered to complement large scale studies of community-level language change, this study aims to explore how changes to family environment and social mobility interact with individual speakers' stylistic practice across life stages. It examines ethnographic interviews of five women, originally from the same area in western Japan, the same high school, and similar socio-economic background, conducted by a single researcher eleven years apart. The chronological and inter-participant comparisons reveal a complex pattern of stylistic practice and stance taking as the women share stories about career, family and relationships with the researcher. The study also discusses audience design in language variation and explores how the participants utilise their discursive repertoires in their interaction with the researcher, whose background is significantly divergent from theirs. (Language across the lifespan, stylistic practice, Japanese)*